PKM of Dryland Maize Cultivation Laponrong Village Amali Subdistrict, Bone Regency - Sandi, Sandi; Erwing, Erwing; Azis, Emmi; Hasanuddin, Hasanuddin; Rianti, Marlia; Yusuf, A.Cakra; Zulkifli, Zulkifli; Yanti, Asia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This service aims to provide knowledge and skills for farmer groups in Laponrong Village, Amali District regarding corn cultivation on dry land. Implementation method with training and demonstration. Implementation of training and mentoring activities for PKM partner groups in Laponrong Village resulted in 85% of partners actively carrying out PKM program training and mentoring. Mitra has understood the technique of cultivating corn on dry land, and the technique of drying corn using sunlight as a heat source.